The acquisition of mechano‐electrical transducer current adaptation in auditory hair cells requires myosin VI - Marcotti, Walter (J Physiol, 2016)
KEY POINTS: The transduction of sound into electrical signals occurs at the hair bundles atop sensory hair cells in the cochlea, by means of mechanosensitive ion channels, the mechano‐electrical transducer (MET) channels. The MET currents decline during steady stimuli; this is termed adaptation and ensures they always work within the most sensitive part of their operating range, responding best to rapidly changing (sound) stimuli. In this study we used a mouse model (Snell's waltzer) for hereditary deafness in humans that has a mutation in the gene encoding an unconventional myosin, myosin VI, which is present in the hair bundles. We found that in the absence of myosin VI the MET current fails to acquire its characteristic adaptation as the hair bundles develop. We propose that myosin VI supports the acquisition of adaptation by removing key molecules from the hair bundle that serve a temporary, developmental role. ABSTRACT: Mutations in Myo6, the gene encoding the (F‐actin) minus end‐directed unconventional myosin, myosin VI, cause hereditary deafness in mice (Snell's waltzer) and humans. In the sensory hair cells of the cochlea, myosin VI is expressed in the cell bodies and along the stereocilia that project from the cells’ apical surface. It is required for maintaining the structural integrity of the mechanosensitive hair bundles formed by the stereocilia. In this study we investigate whether myosin VI contributes to mechano‐electrical transduction. We report that Ca(2+)‐dependent adaptation of the mechano‐electrical transducer (MET) current, which serves to keep the transduction apparatus operating within its most sensitive range, is absent in outer and inner hair cells from homozygous Snell's waltzer mutant mice, which fail to express myosin VI. The operating range of the MET channels is also abnormal in the mutants, resulting in the absence of a resting MET current. We found that cadherin 23, a component of the hair bundle's transient lateral links, fails to be downregulated along the length of the stereocilia in maturing Myo6 mutant mice. MET currents of heterozygous littermates appear normal. We propose that myosin VI, by removing key molecules from developing hair bundles, is required for the development of the MET apparatus and its Ca(2+)‐dependent adaptation.